Pendampingan Kepada Masyarakat Dalam Renovasi Masjid Daarut Taqwa - Soegoto, Eddy Soeryanto; Natalia, Tri Widiati; Sutisnawati, Yayah; Maryati, Mari; Soegoto, Dedi Sulistiyo (Indonesian Community Service and Empowerment Journal (IComSE), 2020)
ABSTRACT Daarut Taqwa Mosque is one of the Jami mosques which is very crowded with various religious activities, such as Friday prayers, Tarawih prayers and Islamic studies routinely carried out by DKM Daarut Taqwa Mosque. The more activities of congregants, DKM Daarut Taqwa Mosque seeks to renovate the mosque to fulfill and accommodate all the congregant who come. The purpose of this article is to show community service activities carried out by the UNIKOM Team in assisting the renovation of the Daarut Taqwa Mosque and assistance in designing the interior and exterior image concept of the mosque. The method of implementation is the design approach, design ideas based on activities, behavior, and activities that take place at the Daarut Taqwa Mosque. The results obtained from the assistance of the construction of the Daarut Taqwa Mosque are the Community Concept as the main concept of the Daarut Taqwa mosque. This concept is to strengthen the "kinship" of the community and illustrate the values of sustainable design that can accommodate various community needs associated with ritual and non-ritual activities, from individuals who eventually become social interactions. It is expected that the Daarut Taqwa mosque to be able accommodate all the activities and many congregants in each Islamic study. So that all concepts of facade, mihrab, landscape, and dome are based on the concept of community. Key words: Community Concept, religious, mosque renovation ABSTRAK Masjid Daarut Taqwa merupakan salah satu masjid Jami yang sangat ramai dengan berbagai kegiatan keagamaan, seperti sholat Jumat, sholat Tarawih dan kajian kajian keilmuan yang rutin dilakukan oleh DKM Masjid Daarut Taqwa. Masjid ini menjadi salah satu pusat kajian Pemuda Hijrah untuk area Bandung Timur. Semakin ramainya aktivitas kegiatan dan padatnya jamaah, DKM Masjid Daarut Taqwa berupaya melakukan renovasi masjid untuk dapat memenuhi dan menampung semua jamaah yang datang. Tujuan penulisan ini adalah menuliskan kegiatan Pengabdian Masyarakat yang dilakukan oleh Tim UNIKOM dalam pendampingan renovasi Masjid Daarut Taqwa dan pendampingan dalam pembuatan konsep gambar interior dan eksterior masjid, sehingga jamaah lebih nyaman dalam melaksanakan kegiatan beragama. Metode pelaksanaan adalah dengan pendekatan desain, gagasan desain berdasarkan pada kegiatan, perilaku, dan aktivitas yang berlangsung di Masjid Daarut Taqwa. Hasil yang didapatkan dari pendampingan pembanguan Masjid Daarut Taqwa ini adalah Konsep Komunitas sebagai konsep utama Masjid Daarut Taqwa. Konsep ini untuk memperkuat "kekerabatan" umat serta menggambarkan nilai-nilai desain keberkelanjutan yang dapat mengakomodasi berbagai kebutuhan masyarakat yang terkait dengan kegiatan ritual dan non ritual, dari individu yang akhirnya menjadi interaksi sosial. Diharapkan Masjid Daarut Taqwa mampu mewadahi seluruh kegiatan dan jumlah jamaah yang cukup banyak disetiap kajian. Sehingga seluruh konsep fasade, mihrab, landscape, dan kubah didasarkan pada konsep komunitas. Kata kunci: Konsep komunitas, keagamaan, renovasi masjid.